A Search for Anti-Carcinogenic and Cytotoxic Effects of Persian Gulf Sea Snake (Enhydrina schistosa) Venom on Hepatocellular Carcinoma Using Mitochondria Isolated from Liver: Cytotoxic effects of Enhydrina schistosa venom - Seydi, Enayatollah; Tajarri, Pardis; Naserzadeh, Parvaneh; Pourahmad, Jalal (Iranian Journal of Pharmaceutical Sciences, 2020)
Common techniques for the treatment of Hepatocellular carcinoma (HCC) have not been successful, and thus the design and discovery of new compounds with better anti-cancer function are needed. Snake venom is among the most important compounds used by researchers to the treatment of various cancers. This study was designed to evaluate the toxicity effect of Persian Gulf snake venom (Enhydrina schistosa) on hepatocytes and mitochondria isolated from HCC rats model. HCC has been induced in rats with diethylnitrosamine (DEN) and 2-acetylaminofluorene (2-AAF). Then rat hepatocytes were isolated with collagen perfusion technique. The results showed that E. schistosa (5, 10, 20 and 40 μg/ml) increases the level of reactive oxygen species (ROS) generation, collapse in mitochondrial membrane potential (MMP), swelling in mitochondria, and cytochrome c release only in hepatocytes and mitochondria isolated from the HCC group. These results proposed that E.schistosa could be considered as a promising complementary therapeutic agent for the treatment of HCC.